Penetration of Payments Banks: A Case Study of India Post Payments Bank in District Muzaffarnagar of UP - Yadav, Nishant; Kumar, Ashok (Journal of Commerce and Trade, 2021)
Rural peoples were dependent on the moneylenders for their financial needs. Government has nationalized the Reserve bank of India in 1949 to regulate the banking sector. In 1955 the Imperial Bank of India was nationalised and named the State Bank of India. This study has been carried out to trace out the penetration of payments bank (A Case study of India Post Payments Bank in district Muzaffarnagar of Uttar Pradesh). Many intense discussions, deliberations and other brain storming sessions were brought in to use to figure out the real picture of impact of IPPB in district Muzaffarnagar. This paper seeks to identify the changes in banking system with the new banking institution i.e Payments bank with the reference to the IPPB in the rural & urban areas of Muzaffarnagar district so that the strong recommendations can be drawn to execute to strengthen the system that will further improve the last mile banking & digital banking. After the demonetarization in 2016, it was realized by the government that cash less economy is required. To lower down the dependence on cash, digital banking was the available alternate. Digital banking is also an important parameter of financial inclusion. This study is expected to bring the light on the penetration of payment ecosystem developed by IPPB.